Glia detect and transiently protect against dendrite substructure disruption in C. elegans - Katherine C. Varandas; Brianna M. Hodges; Lauren Lubeck; Amelia Farinas; Yupu Liang; Yun Lu; Shai Shaham (Nature Communications)
Abstract Glia assess axon structure to modulate myelination and axon repair. Whether glia similarly detect dendrites and their substructures is not well understood. Here we show that glia monitor the integrity of dendrite substructures and transiently protect them against perturbations. We demonstrate that disruption of C. elegans sensory neuron dendrite cilia elicits acute glial responses, including increased accumulation of glia-derived extracellular matrix around cilia, changes in gene expression, and alteration of secreted protein repertoire. DGS-1, a 7-transmembrane domain neuronal protein, and FIG-1, a multifunctional thrombospondin-domain glial protein, are required for glial detection of cilia integrity, physically interact, and exhibit mutually-dependent localization to and around cilia, respectively. Glial responses to dendrite cilia disruption transiently protect against damage. Thus, our studies uncover a homeostatic, protective, dendrite-glia signaling interaction regulating dendrite substructure integrity.